A Design of Intelligent Garbage Bin System. Issue 1 (July 2021) - Zha, Yang; Zhou, Min; Yang, Jiale; Yang, Yongjie
Abstract: Garbage classification is more and more significant recent years. In order to promote the implementation of garbage classification and the improvement of intellectualization of urban sanitation work, a new type of intelligent garbage bin system is designed, which includes the bottom control part, android app and IOT cloud platform. Firstly, the system controls the inlets of intelligent garbage bin through interaction with android app, which realizes the function of ordinary garbage can. On top of that, the bottom control part collects all kinds of data of garbage bin by using some external sensors. And then the data will be reported to Android and Android will report that to cloud platform. Cloud platform server then transmits data to monitoring platform, which facilitates data statistics and the removing of garbage. By deploying the system, garbage classification can be promoted and the status of garbage can be effectively monitored, which will significantly improve garbage recovery efficiency and sanitation work level.